CeAid: a smartphone application for logging and plotting Caenorhabditis elegans assays. Issue 10 (15th July 2021) - Sohrabi, Salman; Moore, Rebecca S; Murphy, Coleen T
Abstract: Caenorhabditis elegans is used as a model organism to study a wide range of topics in molecular and cellular biology. Conventional C. elegans assays often require a large sample size with frequent manipulations, rendering them labor-intensive. Automated high-throughput workflows may not be always the best solution to reduce benchwork labor, as they may introduce more complexity. Thus, most assays are carried out manually, where logging and digitizing experimental data can be as time-consuming as picking and scoring worms. Here we report the development of Ce Aid, C. elegans Application for inputting data, which significantly expedites the data entry process, utilizing swiping gestures and a voice recognition algorithm for logging data using a standard smartphone or Android device. This modular platform can also be adapted for a wide range of assays where recording data is laborious, even beyond worm research.